Effect of Technology Based Financial Innovations on Non-Interest Income of Commercial Banks in Kenya - Alubisia, L’souza Boniface; Githii, Wainaina; Mwangi, Mirie (European Scientific Journal, ESJ, 2018)
Technology based financial innovation has had a great impact on the financial industry as a whole over the past few decades. It has presented the banking sector with an opportunity to increase the revenue base. This study intended to identify the impact of technology based financial innovation on non-interest income in Kenyan commercial banks. The study investigated how the adoption of ATMs and Cards, Internet and Mobile Banking and use of Funds Transfer Systems such as RTGS and EFT has impacted the non-interest income of commercial banks in Kenya. Descriptive research design was utilised. The study found that technology based financial innovation has significant effect on the non-interest income earned by commercial banks in Kenya. It recommends all stakeholders in commercial banks to take any investments made towards technology based financial innovation products as a strategy to improve non-interest income